2016
DOI: 10.1007/s00264-016-3144-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Femoral shortening osteotomy in total hip arthroplasty for severe dysplasia: a comparison of two fixation techniques

Abstract: Fixation of the removed femoral segment with a cable provided adequate rotational stability and decreased the operating time, leading to early union at the osteotomy site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Many osteotomy techniques have been reported, such as the oblique, transverse, step‐cut, V‐shaped, and double‐chevron techniques. In this series, we used transverse subtrochanteric shortening osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many osteotomy techniques have been reported, such as the oblique, transverse, step‐cut, V‐shaped, and double‐chevron techniques. In this series, we used transverse subtrochanteric shortening osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nonosteotomy techniques, subtrochanteric shortening osteotomy can simplify reduction and ensure correction of the femoral deformity, but it may lead to complications such as dislocation, loosening, osteotomy site nonunion, and instability. Transverse osteotomy, which has a limited bony contact area and lacks inherent rotational stability, is especially vulnerable to these possible complications. To address these concerns, the longitudinally split fragments from the resected cylindric femur bone were placed around the osteotomy site as a structural allograft, fixed with cerclage wires, and augmented by morselized cancellous bone autografts from the resected femoral heads to accelerate bone union of the osteotomy site and enhance rotational stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to these osteotomies, transverse osteotomy, which was performed in our series, has some advantages such as technical simplicity in terms of the osteotomy technique, adjusting the anteversion angle and minimal periosteal damage at the osteotomy site, and preserving the proximal femoral metaphysis [27] , [28] . However, transverse subtrochanteric shortening osteotomy has several potential complications such as osteotomy site nonunion and instability due to limited bony contact area and lack of inherent rotational stability [6] , [29] . Reikerås et al [30] reported that osteotomy site nonunions are caused by insufficient rotational stability of THA associated with transverse osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Screw-plate fixation is a priority selection due to avoiding borehole in non-medullated bone, but some limitation still disturbs surgeons, such as refracture, accumulative stress to newborn site. [ 4 ] Even a later retrospective study [ 16 ] illuminated that fixation with a cable leads to an earlier union than that with plate and screw in the osteotomy. In this case, we utilized a locked plate system (LISS) to enhance stability in the osteopetrotic patient.…”
Section: Treatment Of Fracture In Osteopetrosismentioning
confidence: 99%